Libya After Qaddafi Lessons and Implications for the Future - Chivvis, Christopher S. (Research Reports, 2014)
The 2011 overthrow of Libyan dictator Muammar Qaddafi by internationally backed rebel groups has left Libya's new leaders with a number of post-conflict challenges, including establishing security, building political and administrative institutions, and restarting the economy. This report assesses these challenges, the impact of the limited international role in efforts to overcome them, and possible future roles for the international community.